Hubungan Pengetahuan dan Sikap Ibu Nifas Tentang Perawatan Luka Perineum di Rumah Bersalin Rossita Pekanbaru 2017 - Ratih, Rini Hariani (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
Indonesias demographic and health surveys (SDKI) tahun2012 AKI (related to pregnancy, childbirth, and childbirth) amounted to 359 / 100,000 live births. This figure is still quite far from the target to be achieved in 2015. AKI in Riau Province in 2010 amounted to 109.9/100,000 live births, experiencing an increase in 2014 of 124.5/100,000 live births. The immediate causes associated with maternal death are complications in pregnancy, childbirth, and childbirth are not handled properly and on time. Maternal mortality during childbirth is usually caused by postpartum infections, this is due to lack of wound care. Objective of research To know relation of knowledge and attitude of mother about perineum wound care. This research uses quantitative research type. The research design used was cross sectional. The population in this research is all postpartum who live in work area RB Rosita which amounted to 50 people. Based on the analyst by using statistical test chi squer more than 0,05 it is known that p value of 0,02 for knowledge variable hence small value p value from 0,05  concluded that there is significant correlation between knowledge to perineum wound care. While statistic test results obtained P value less than 0.05 (P = 0.04) for attitude variable, it can be concluded that there is a relationship between postpartum attitude to perineal wound care. Keywords: Knowledge and Attitude, Nifas, Perineal Wound Care